Plasma cytokine levels and risks of abdominal aortic aneurysms: A population-based prospective cohort study. (May 2015) - Liao, Mengyang; Liu, Cong-Lin; Lv, Bing-Jie; Zhang, Jin-Ying; Cheng, Longxian; Cheng, Xiang; Lindholt, Jes S.; Rasmussen, Lars M.; Shi, Guo-Ping
Abstract: Background. Abdominal aortic aneurysm (AAA) is characterized by inflammatory cell accumulation in AAA lesions that produce inflammatory cytokines and advance its pathogenesis. Peripheral cytokines may predict the degree or risk of AAA. Methods and results. ELISA determined plasma interleukin-6 (IL6), IL10, IL17A, IFN-γ, and C-reactive protein (CRP) from 476 AAA patients and 200 controls. AAA patients had lower IL6, IFN-γ, IL10, IL17A, and higher CRP than controls. IL10 correlated positively with IFN-γ, IL17A, or IL6, but not CRP in control or AAA populations. IL10 associated negatively with systolic blood pressure, whereas CRP associated positively with diastolic blood pressure and body mass index. CRP was an independent AAA risk factor and correlated positively with aortic diameters before and after adjustments for other risk factors. IFN-γ, IL17A, and CRP correlated positively with cross-sectional AAA area after adjustment. IL10 correlated positively with AAA growth rate before and after adjustment. The risk of death doubled in AAA patients with CRP levels above the median. Conclusions. Reduced IFN-γ, IL10, and IL17A in AAA patients, positive correlations of IFN-γ and IL17A with cross-sectional AAA area, IL10 with AAA growth rate, and IL10 with IFN-γ and IL17A suggest combined Th1, Th2, and Th17 immune responses in human AAAs.